The International Spillover Effect of Import Trade on Energy Efficiency in the Post-COVID-19 Era: Evidence From China - Hao, Xiaoli; Wang, Xinhui; Xue, Yan (Frontiers in Energy Research, 2022)
China is in a transition period—its government has been expanding imports and pushing itself to shift from a world factory to a world market. One of the aims is to promote energy reform and ensure energy security. Taking the resource-based regions of China as objects, based on 2003–2017 panel data, this paper investigates energy efficiency loss by the stochastic frontier approach and the effects of different technical inefficiency items. Surprisingly, quantitative results show that 99.9% energy efficiency loss in these regions is caused by technical inefficiency (which had never been found and discussed in previous studies). However, this does not mean that China’s efforts to expand imports as a way to improve energy efficiency and energy security are undesirable. Instead, interestingly, it is import (−0.083***) rather than industrial structure (0.524***) that can significantly reduce energy efficiency loss. Then, it employs the counter-fact test to quantify the positive accelerating effect of human capital (average as high as 4.1%) as a key factor of absorptive capacity in the technology spillover. Lastly, it puts forward the corresponding policy suggestions in energy fields, to solve the problem effectively, especially the “comprehensive technology spreading center” and “innovative three-dimensional talent supplementary and flow mechanism.”